AB0508 EFFICACY AND SAFETY OF TNF-Α ANTAGONISTS AND TOCILIZUMAB IN TAKAYASU ARTERITIS: MULTICENTER EUROPEAN RETROSPECTIVE STUDY OF 203 PATIENTS. (13th June 2020) - Mekinian, A.; Vautier, M.; Resche-Rigon, M.; Dagna, L.; Sciascia, S.; Olivier.Espitia@chu-Nantes.Fr, O. E. N. F.; Cacoub, P.; Fain, O.; Saadoun, D.
Abstract : Background: Takayasu arteritis (TA) is a chronic inflammatory large-vessel vasculitis, predominantly affecting the aorta and its main branches Objectives: To assess safety and efficacy of biologics (i.e. TNF-α antagonists and tocilizumab) in patients with Takayasu arteritis (TA). Methods: We conducted a retrospective multicenter study in referral centers from Europe and several countries in the world about biological-targeted therapies in Takayasu arteritis during the period from January 2017 to September 2019. Results: Retrospective multicenter study of characteristics and outcome of 49 TA patients [80% of females; median age 42 [20-55] years] treated by TNF-α antagonists (80%) or tocilizumab (20%)] and fulfilling ACR and/or Ishikawa criteria. Factors associated with complete response were assessed. Eighty-eight percent of TA patients were inadequately controlled with, or intolerant to, conventional immunosuppressive therapy [median number of 3 (1-5)]. Overall response (i.e. complete and partial) to biological-targeted treatments at 6 and 12 months was of 75% and 83%, respectively. There were a significantly lower C-reactive protein levels at initiation of biological-targeted treatments [22 [10-46] mg/l vs 58 [26-76] mg/l, (p=0.006)] and a trend toward lower immunosuppressants drugs used prior biologics (p=0.054) in responders (i.e. complete and/or partial responders) relative to non-responders to biological-targeted treatments. C-reactive protein levels and daily prednisone dosage significantly decreased after 12 months of biological-targeted treatments [30 vs 6 mg/l, p<0.05 and 15 vs 7.5 mg, p<0.05, at baseline and at 12 months, respectively]. The 3-year relapse free survival was of 90.9% (83.5-99) over biologic treatment period compared to 58.7% (43.3-79.7) (p=0.0025) with DMARDs. No difference was found relative to efficacy between TNF-α antagonists and tocilizumab. After a median follow-up of 24 [2-95] months, 21% of adverse effects occurred, with biological-targeted treatments discontinuation in 6.6% of cases. Conclusion: This nationwide study shows high efficacy of biological-targeted treatments in refractory TA patients with an acceptable safety profile. Acknowledgments: NO Disclosure of Interests: Arsene Mekinian: None declared, Mathieu Vautier: None declared, Matthieu resche-rigon: None declared, Lorenzo Dagna Grant/research support from: Abbvie, BMS, Celgene, Janssen, MSD, Mundipharma Pharmaceuticals, Novartis, Pfizer, Roche, SG, SOBI, Consultant of: Abbvie, Amgen, Biogen, BMS, Celltrion, Novartis, Pfizer, Roche, SG, and SOBI, Savino Sciascia: None declared, olivier.espitia@chu-nantes.fr olivier.espitia@chu-nantes.fr: None declared, Patrice cacoub: None declared, olivier fain: None declared, david Saadoun: None declared